Research on the Techniques of High Power SiC-MOSFET Driver - ZHOU Shuai; ZHANG Xiaoyong; RAO Peinan; ZHANG Qing; SHI Hongliang (机车电传动)
In order to adapt to the characteristics of SiC-MOSFET, such as faster switching speed, lower loss but lower threshold voltage and weaker short-circuit capacity compared to Si-IGBT, the key techniques of SiC-MOSFET driver was analyzed, including drain voltage active clamping, bridge-arm crosstalk suppression, and over-current detection etc, as well as the test aiming at the driver for Mitsubishi SiC-MOSFET module. The results showed that the mirror-current sensing method could give a good protection for SiCMOSFET, and the active clamping could reduce the high voltage surges across the high current turned-off.